Identifying New International Customers for Alfândega Porto Congress Centre - Dhekra Lachheb (My University, 2017)
This report describes the internship I carried out at Alfândega Porto Congress Center (APCC) that lasted for a period of 400 hours, between the 12th of September and the 21st of November. The APCC is a leading event management organization in Porto that hosts events from domestic and foreign customers. Besides, the venue offers internship opportunities to the students in need for practical knowledge about how the congress centers operate in general. The internship as an opportunity to relate what we have learnt during the academic course and what we learn in the practical framework. Thus, during my master internship, I had a first professional approach to the field of events organization. I was then, in charge of four main tasks related to event organization, marketing and commercial activities, and finally conducting and analyzing a survey. All the activities that were carried out had an objective of contributing to attract new international customers to the venue. The purpose of this report is to explore new ways for bringing new international customers for the APCC. For that goal, this study starts with the organization diagnosis and problematic, followed by a technical-scientific justification and going through the methodology and the activities developed in the internship, ending with its reflection and recommendations, which can contribute for a better operation in the venue in terms of marketing.